The mir‐200 family regulates key pathogenic events in ascending aortas of individuals with bicuspid aortic valves. (2nd October 2018) - Maleki, S.; Cottrill, K. A.; Poujade, F.‐A.; Bhattachariya, A.; Bergman, O.; Gådin, J. R.; Simon, N.; Lundströmer, K.; Franco‐Cereceda, A.; Björck, H. M.; Chan, S. Y.; Eriksson, P.
Abstract: Background: An individual with a bicuspid aortic valve (BAV) runs a substantially higher risk of developing aneurysm in the ascending aorta compared to the normal population with tricuspid aortic valves (TAV). Aneurysm formation in patients with BAV and TAV is known to be distinct at the molecular level but the underlying mechanisms are undefined. Here, we investigated the still incompletely described role of microRNAs (miRNAs), important post‐transcriptional regulators of gene expression, in such aortic disease of patients with BAV as compared with TAV. Methods and Results: Using a system biology approach, based on data obtained from proteomic analysis of non‐dilated aortas from BAV and TAV patients, we constructed a gene‐interaction network of regulatory microRNAs associated with the observed differential protein signature. The miR‐200 family was the highest ranked miRNA, hence potentially having the strongest effect on the signalling network associated with BAV. Further, qRT‐PCR and ChIP analyses showed lower expression of miR‐200c, higher expression of miR‐200 target genes, ZEB1/ZEB2 transcription factors, and higher chromatin occupancy of the miR‐200c promoter by ZEB1/ZEB2 in BAV patients, indicating a miR‐200c/ZEBs negative feedback loop and induction of endothelial/epithelial mesenchymal transition (EndMT/EMT). Conclusion: We propose that a miR‐200‐dependent process of EndMT/EMT is a plausible biological mechanism rendering the BAV ascending aorta more prone to aneurysm development. Although initially supported by a miR‐200c/ZEB feedback loop, this process is most probably advanced by cooperation of other miRNAs.